Al-Munajat fi Al-Adab Al-‘Arabiy An-Nijiriy (Dirasah Uslubiyyah Limunajat Zakariya Idris Oboh Husain) - Kankawi, Uthman Idrees (UIN Maulana Malik Ibrahim Malang, 2021)
هذا البحث يرصد دراسة مناجيات البروفيسور زكريا إدريس أوبو حسين، دراسة أسلوبية، للوقوف على قدرة الكاتب في رسم المشاهد المختلفة في حالات النفس الإنسانية، والكشف عن مستويات المناجيات النصية، والتقديم لدلالات ما خلف النص بوصفه نصاً أدبياً خاضعاً للقراءة والتأويل. وقد تناولت الدراسة كتب مناجاته في مستوياتها الصوتية والتركيبية والدلالية محاولة لإجراء الدراسة الأسلوبية عند كل مستوى، فقد أورد البروفيسور الاستعارات والتشبيهات والكنايات بشكل تفاعلي مع الجو الملائم لكل مناجاة، وأهمية هذا البحث تظهر في قلة أمثاله في المكتبات التي تستقري مثل هذه النصوص الإسلامية الشريفة، والتي تستحق لفت النظر. وتم تقسيم الدراسة إلى أربعة مباحث، سبقهم ملخص، ومقدمة، وفي الخاتمة تم تسجيل أهم النتائج فضلا عن المصادر والمراجع، والله المستعان. Professor Zakariyau Idrees Oboh Oseni, is one of the prominent figures of Arabic and Islamic literature in Nigeria, working with University of Ilorin in Nigeria as an exemplary teacher, a writer and even a Critical critic. His poetic talent, literary ability, linguistic wealth, knowledge of the Noble Qur’an and the Prophet’s Sunnah, made him succeed in the Art of Munajat, and succeed as a sincere scholar who raises the nation a high-level education. This Research aims to study the Munajat (Monologues) of Professor Zakariyau Idrees Oboh Oseni as a stylistic study, to determine the writer›s ability to draw different scenes in cases of the human soul, to reveal the levels of textual Monologues, and to present the implications of what is behind the text as a literary text subject to reading and interpretation. The Study dealt with his Monologue books in their phonetic, structural and semantic levels, an attempt to conduct a stylistic study at each level. This approach includes a set of principles and procedures that aid the study of the text as a scientific study, through method analysis. The research is divided into three sections, preceded by a summary, followed by a conclusion.